2010
DOI: 10.4067/s0718-27912010000100005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compost and Sewage Sludge on Soil Biologic Activities in Salt Affected Soil

Abstract: Saline soil was amended with 13.3 and 26.6 g kg -1 of Municipal Solid Waste (MSW) compost or sewage sludge, and arylsulphatase (ARY), phosphatase (PHO), dehydrogenase (DEH), β-glucosidase (β-GLU), urease (URE) and catalase (CAT) activities as well as physical-chemical properties were determined after 70 day of incubation under laboratory conditions. MSW compost and sewage sludge significantly improved soil physical-chemical properties, especially carbon and nitrogen contents. Accordingly, overall enzyme activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 23 publications
3
38
0
1
Order By: Relevance
“…The result in the reduction in bulk density by the amendments was not only due to the addition of less dense organic material, but also due to the increase in soil aggregate stability [40] (Figure 6(b)). Previous studies have shown that the application of sewage sludge increased organic carbon in saline and salinized soil [41,42], subsequently increased aggregate stability in saline-sodic and salinized soil [ 42,43], and decreased bulk density in salt-soil and salinized soil [9,42]. Topsoil salinity in mudflat salt-soil decreased as a result of increasing soil aggregate stability and decreasing bulk density.…”
Section: Discussionmentioning
confidence: 99%
“…The result in the reduction in bulk density by the amendments was not only due to the addition of less dense organic material, but also due to the increase in soil aggregate stability [40] (Figure 6(b)). Previous studies have shown that the application of sewage sludge increased organic carbon in saline and salinized soil [41,42], subsequently increased aggregate stability in saline-sodic and salinized soil [ 42,43], and decreased bulk density in salt-soil and salinized soil [9,42]. Topsoil salinity in mudflat salt-soil decreased as a result of increasing soil aggregate stability and decreasing bulk density.…”
Section: Discussionmentioning
confidence: 99%
“…Different alternatives for the disposal of such waste have been proposed at the international level, including the option of recycling waste in agricultural soils (Fytili and Zabaniotou, 2008;Fernández et al, 2007), as a way to help degraded soils restore their productivity (Esparza et al, 2004;Schleef et al, 2004;Aravena et al, 2007;Lakhdar et al, 2010). It is important to note that at least 46% of the Chilean agricultural area (34.5 million hectares) has certain degree of erosion of which 33% is severely affected (Esparza et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Sludge acts as a source of essential crop nutrients (Smith and Tibbett, 2004;Ferreiro-Domínguez et al, 2011), stimulates microbial activity (Boyle and Paul, 1989;Lakhdar et al, 2010), immobilises toxic elements in soil (Neunhäuserer et al, 2001), improves soil structure, and minimises soil erosion and runoff (Ojeda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%